Analysis of risk factors associated with recurrence of acute pericarditis in patients diagnosed in the emergency room. (25th November 2020) - Izquierdo Ribas, M; Martinez-Nadal, G; Cepas, P; Aldea, A; Matas, A; Lopez-Sobrino, T; Lopez-Barbeito, B; Andrea, R; Miro, O
Abstract: Background: Around 5% of patients consulting to the emergency room (ER) for non-ischemic thoracic pain are diagnosed of acute pericarditis (AP). The good prognosis of this pathology is well known, with a mortality of 1% and a low incidence of serious complications, which has led the research to focus on recurrences. Female sex, corticoid treatment and treatment adherence are related with higher risk of recurrence. Colchicine has been associated with less recurrences. Purpose: To analyse the factors associated with recurrence after the diagnosis of AP in the ER of a third-level hospital. Methods: Retrospective review of ER consultations oriented as AP, prospectively documented during 10 years (2008–2018). In 2019, a follow up was done in order to identify the recurrences and to search for associated factors (univariate and multivariate analysis). Results: 610 patients were diagnosed of AP, 175 (29%) recurrences were documented. Factors associated with an increased risk of recurrence were: previous AP, immunosuppression or history of autoimmune disease, fever or increased acute-phase reactants (CRP; ESR), hospitalization and corticoid treatment. Factors associated with less risk of recurrence were: age, non-steroidal anti-inflammatory drug (NSAID) treatment and idiopatic/viral etiology. No association with sex or colchicine treatment was identified. Multivariate analysis identified 3 factors that were independently associated with the risk of recurrence in a direct way: previous history of AP, [OR (IC95%): 2.09 (1.11–3.92)]; increased CRP [OR (IC95%): 1.09 (1.03–1.15)]; hospitalization [OR (IC95%): 2.65 (1.07–6.58)]. 2 factors were inversely associated with the risk of recurrence: age [OR (IC95%): 0.98 (0.96–0.99)]; NSAID treatment [OR (IC95%): 0.56 (0.32–0.97)]. Conclusions: 29% of the patients were readmitted to the ER for an AP recurrence. Previous AP, increased CRP and the need of hospitalization were associated with a higher risk of recurrence. Age and NSAID treatment, on the other hand, were associated with less risk of recurrence. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Ajuts per la Recerca Josep Font